An enzyme-based protocol for cell-free synthesis of nature-identical capsular oligosaccharides from Actinobacillus pleuropneumoniae serotype 1 - Budde, Insa (J Biol Chem, 2020)
Actinobacillus pleuropneumoniae (App) is the etiological agent of acute porcine pneumonia and responsible for severe economic losses worldwide. The capsule polymer of App serotype 1 (App1) consists of [4)-GlcNAc-β(1,6)-Gal-α-1-(PO(4)-] repeating units that are O-acetylated at O-6 of the GlcNAc. It is a major virulence factor and was used in previous studies in the successful generation of an experimental glycoconjugate vaccine. However, the application of glycoconjugate vaccines in the animal health sector is limited, presumably because of the high costs associated with harvesting the polymer from pathogen culture. Consequently, here we exploited the capsule polymerase Cps1B of App1 as an in vitro synthesis tool and an alternative for capsule polymer provision. Cps1B consists of two catalytic domains, as well as a domain rich in tetratricopeptide repeats (TPRs). We compared the elongation mechanism of Cps1B with that of a ΔTPR truncation (Cps1B-ΔTPR). Interestingly, the product profiles displayed by Cps1B suggested processive elongation of the nascent polymer, whereas Cps1B-ΔTPR appeared to work in a more distributive manner. The dispersity of the synthesized products could be reduced by generating single-action transferases and immobilizing them on individual columns, separating the two catalytic activities. Furthermore, we identified the O-acetyltransferase Cps1D of App1 and used it to modify the polymers produced by Cps1B. Two-dimensional NMR analyses of the products revealed O-acetylation levels identical to those of polymer harvested from App1 culture supernatants. In conclusion, we have established a protocol for the pathogen-free in vitro synthesis of tailored, nature-identical App1 capsule polymers.